Oral myiasis involving palatal mucosa of a young female - Yadav, Suresh (Medknow Publications & Media Pvt Ltd, 2014)
In literal terms myiasis is the invasion of the tissues and organs of human beings by fly larvae. This phenomenon is well documented in the skin, especially among animals and people in developed and developing countries. When the tissues of oral cavity are invaded by the parasitic larvae of flies, the condition is called as oral myiasis. With the paper we are presenting a case of 19-year-old female suffering from oral myiasis of upper lip and palate. The treatment consisted of manual removal of the larvae, surgical debridement of the wound and oral therapy with doxycycline used as a locally acting drug for faster and better recovery.